2013
DOI: 10.4103/0972-2327.112475
|View full text |Cite
|
Sign up to set email alerts
|

Nummular headache and pituitary lesion: A case report and literature review

Abstract: Nummular headache (NH) is a newly categorized headache disorder characterized by a consistent clinicographics in each attack. Currently, it is considered as a primary headache disorder due to epicranial neuralgia but the pathomechanism is still unknown. We report a woman, whose recurrent NH subsided after trans-sphenoidal surgery for her pituitary oncocytoma. The recovery of NH in this patient encourages the central mechanism for NH occurrence. After a review of literature concerning, NH and intracranial secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
(25 reference statements)
0
5
0
2
Order By: Relevance
“…In an extensive case series, Cuadrado and his colleagues reported that nummular headache was associated with a local increase in pain sensitivity to mechanical stimulation (reduced pressure pain thresholds [PPTs]) confined to the symptomatic area [14]. Although the pain is asserted to originate from epicranial tissues including the skull, scalp, vessels, and nerves [1517], some nummular headaches have been described as “symptomatic nummular headaches”, which implies that they might be secondary to underlying structural lesions or other causes, such as subtentorial meningioma [10], pituitary lesion [18], or arachnoid cysts [19]. These observations represent the secondary form of nummular headache.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive case series, Cuadrado and his colleagues reported that nummular headache was associated with a local increase in pain sensitivity to mechanical stimulation (reduced pressure pain thresholds [PPTs]) confined to the symptomatic area [14]. Although the pain is asserted to originate from epicranial tissues including the skull, scalp, vessels, and nerves [1517], some nummular headaches have been described as “symptomatic nummular headaches”, which implies that they might be secondary to underlying structural lesions or other causes, such as subtentorial meningioma [10], pituitary lesion [18], or arachnoid cysts [19]. These observations represent the secondary form of nummular headache.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to spontaneous pain, there may be sensory disturbances in the affected area. The description given for these disturbances is diverse, but in one form or another they can be found in many cases of NH (1,4,6,(10)(11)(12)(13)(14)16,(20)(21)(22)(23)(24)(25)(26)(27)29,31,35,39,41,42,47,48,51,53,(57)(58)(59)(60)(63)(64)(65)(66). In one of the largest series, sensory symptoms or signs were detected in more than 40% of cases (33).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Iako može koegzistirati sa drugim primarnim glavoboljama, ona ima sopstvene karakteristike i nezavistan tok. (4). Pogođeno područje najčešće pokazuje razne kombinacije simptoma kao što su :hipestezije, dizestezije, parestezije, alodinije i/ili osetljivosti.…”
Section: Prikaz Slučajaunclassified
“…Naš prikaz pokazuje da postoje značajne diferencijalno dijagnostičke poteškoće koje su vezane za još jedan klinički entitet dermatološke geneze. U literaturi Numularna glavobolja nije retka pojava i opisani su slučajevi različitih precipitirajućih događaja, među kojima prednjači trauma glave (6,8), strukturne lezije, virusne infekcije (7), dermatološke lezije… (9) Lichen planopilaris (LPP) je posebna forma lichen planus-a (LP) lokalizovanog na područjima kože obraslim dlakom, pre svega, u kapilicijumu, koja može da izazove ireverzibilnu cikatrijalnu, tj. ožiljnu alopeciju.…”
Section: Prikaz Slučajaunclassified